Magnetospheric ULF waves driven by external sources - Agapitov, O.V.; Cheremnykh, O.K. (Advances in Astronomy and Space Physics, 2013)
The multi-spacecraft missions (Cluster and THEMIS) observations allowed to collect large data base for Ultra Low Frequency (ULF) waves properties, their localization, and sources. Here we focused mainly on these recent results. Studies of the source and characteristics of ULF waves can help in the understanding of the interaction and energy transport from the solar wind to the magnetosphere. In the presented paper peculiarities of the ULF waves are presented in depends of their generation source: surface magnetopause instabilities, magnetospheric cavity modes, and solar wind sudden impulses (SI). Permanent observations of the ULF waves involve existence of the permanent source and, as the previous studies showed, the contributions to Pc4-Pc5 ULF wave power from the external sources are larger than the contribution from internal magnetosphere sources. The Kelvin-Helmholtz instability (KHI) can generate classical ULF resonant waves with spatially localized amplitude maximum on the magnetosphere flanks. As observations show the constraint satisfaction of KHI development is quite rare. SI in the solar wind dynamic pressure generate ULF waves with different polarization and frequency close to the frequency of the local field line resonance (FLR). Wide range of temporal and amplitude characteristics of the solar wind dynamics can generate magnetosphere cavity modes and magnetosonic perturbations which penetrate through the magnetosphere and can couple with the local FLR modes. The observed dependence of ULF waves properties on their localization corresponds well to these sources and their occurrence.